C-Section in Uncorrected Ventricular Septal Defect and Pulmonary Hypertension Management in Anesthesia Perspective - Febrianti, Rizki Fitria; Supraptomo, Robertus Theodorus (Faculty of Medicine, Brawijaya University, 2022)
Background: Pregnancy with cardiac defects and pulmonary hypertension happen 0.2% to 3% and is correlated with valuable hemodynamic burden due to cardiocirculatory changes which becomes a remarkable indirect cause of maternal mortality and poor fetal outcome. Ventricular septal defect (VSD) is one of the most common forms of heart disease among pregnant women, meanwhile the VSD-specific pregnancy data are insufficient. This case report addresses the anesthetics management for patient with uncorrected ventricular septal defect and pulmonary hypertension.Case: A 30-year-old multigravida with 37 weeks of gestation weighing 52 kg referred elective cesarean section and tubal ligation. She was compos mentis with arterial oxygen saturation was 87-88% room air. A grade IV/VI systolic murmur was heard at the second intercostal space of the left midclavicular line and the punctum maximum at the fourth intercostal spaces of the left sternal border. She had cyanotic in all of her extremities and clubbing fingers. Other examination is within normal limit. Titrated epidural was given at L1-2 level with parenteral levobupivacaine and fentanyl used as an adjuvant. The patient was stable during the surgery. Both maternal and fetal had a good outcome. The patient was discharged at the 7th day after surgery.Conclusion: To achieve a good outcome from management of the high-risk obstetric patients requires multidisciplinary approach involving anesthetist, obstetrician, and cardiologist in planning and managing the case.